Evaluation of road cross-section design using driving simulation - Ng, Kay Guan (2018)
Effective land usage is often a crucial and important concern for land-scare and highly urbanised places like Singapore. Road transport networks have been considered as a possible area of optimisation through the minimisation of lane widths. Any potential changes to road cross-section design hinges on its effect to driving behaviour of road users especially with safety. Driving behaviour of users shows the natural tendencies of drivers to act in certain ways without external influences. It can vary with multiple factors like age, gender and experience. This directly affects drivers’ speed control, reaction to differing lane widths and also safety.